Nations, cultures et sociétés d’Europe centrale aux XIXe et XXe sie`cles. Mélanges offerts a` Bernard Michel, (ed.) Catherine Horel: Paris 2006, Publications de la Sorbonne, 286 s., ISBN 2-85944-550-1 - Horská, Pavla (Dějiny – teorie – kritika, 2006)
Review